Photocatalytic degradation of gaseous toluene over ZnAl2O4 prepared by different methods: A comparative study - Li, Xin Yong; Zhu, Z.; Zhao, Q.; Wang, L. (2011)
The development of a " green" treatment process for typical indoor pollutants such as toluene is greatly desirable. In this study, ZnAl2O4 nanoparticles were prepared via three different routes, i.e., solvothermal, citrate precursor and hydrothermal methods. Their structural properties were systematically investigated by X-ray powder diffraction (XRD), scanning electronic microscopy (SEM), energy-dispersive X-ray spectra (EDX), Brunauer-Emmett-Teller (BET), UV-vis diffuse reflectance spectroscopy (DRS), and Fourier transform infrared spectroscopy (FT-IR) techniques. The photo-induced charge separation in the samples was demonstrated by surface photovoltage (SPV) measurement. The photocatalytic performances of the ZnAl2O4 samples and nanostructured TiO2 samples were comparatively studied by the degradation of gaseous toluene under UV lamp irradiation in in situ FTIR reactor. The results indicated that the sample synthesized by facile solvothermal method exhibited about 90% photocatalytic efficiency of toluene. The toluene was mineralized into carbon dioxide and water as the major species. The photocatalytic oxidation of gaseous pollutant over UV-illuminated ZnAl2O4 is a promising technique for air purification. © 2011 Elsevier B.V.